A GUIDANCE ON IMPLEMENTING EARLY CHILDHOOD DEVELOPMENT ASSESSMENT : Assessment Kurmer - tilawati, nentih (International Conferences on Early Childhood Education Proceedings, 2024)
The "Implementation of Early Childhood Development Assessment in Sawah Besar District, Central Jakarta" aims to provide guidance and understanding to PAUD teachers about the principles, functions, and types of assessment. Through workshops and mentoring, teachers are expected to effectively implement child development assessments in daily learning activities. The methods used include training, discussion, and consultation. The results show an increase in teachers' understanding and skills in conducting assessments. This activity positively impacts early childhood development in the area.